Getting Jacked and Burning Fat: Examining Doping and Gender Stereotypes in Canadian University Sport - Weaving, Charlene; Teetzel, Sarah (Journal of Intercollegiate Sport, 2014)
In this paper, the authors analyze the results of a three-year qualitative study examining Canadian female and male university student athletes’ perceptions of gender and doping. Student athletes (n = 38) discussed their perceptions of doping, gender, and sport during in-depth, semistructured interviews. The results demonstrate the extent that student athletes continue to draw on gender stereotypes in assessing acceptable and unacceptable substance use in sport. Many of the student athletes interviewed acknowledged or applied extensive gender stereotyping in discussing their understanding of femininity and masculinity in sport. Women athletes, in particular, indicated they were hesitant to use both banned and permitted ergogenic supplements out of fear of becoming too muscular or masculine, while several male athletes expressed feeling pressure to appear muscular, especially if they wanted to be successful in traditionally male-dominated sports such as football. Applying previous theoretical work Lock by (2003) and Bartky (1990) to the themes resulting from the interviews, the authors argue that student athletes’ attitudes toward doping remain engulfed in gender stereotypes. Because doping culture in the Canadian university system is entangled with gender stereotyping, doping education and prevention programs would benefit from taking these gender stereotypes into account, rather than pretending they do not exist.